2015
DOI: 10.4025/actascianimsci.v37i1.24466
|View full text |Cite
|
Sign up to set email alerts
|

<b>Mesquite pod meal in sheep diet: intake, apparent digestibility of nutrients and nitrogen balance

Abstract: ABSTRACT. Eight Santa Ines sheep were assigned to two 4 x 4 Latin squares, to evaluate the effects of replacing elephant grass silage with different levels of mesquite pod meal (MDM) (15, 30 and 45% DM) on intake, apparent digestibility of dry matter (DM), organic matter (OM), crude protein (CP), ether extract (EE), acid detergent fiber (ADF), neutral detergent fiber (NDF), total carbohydrates (TC) and non-fiber carbohydrates (NFC) and the nitrogen balance. There was a linear increase (p < 0.05) in the intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The difficulty obtaining a regular supply of good‐quality feedstuffs all year long is one of the major obstacles faced by sheep farmers in semi‐arid regions of the world. Therefore, forage preservation is an alternative for animals reared in regions with long periods of drought, as it can prevent weight losses and declines in production performance (Santos et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty obtaining a regular supply of good‐quality feedstuffs all year long is one of the major obstacles faced by sheep farmers in semi‐arid regions of the world. Therefore, forage preservation is an alternative for animals reared in regions with long periods of drought, as it can prevent weight losses and declines in production performance (Santos et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…However, both CS and CSI favored the intake of most nutrients by the sheep when compared with FC1 and FC2. In many cases, decreases in nutrient intake may be due to nutritional factors such as elevated or low NDF contents or excess NFC (Santos et al, 2015;Sousa et al, 2018). In addition to having very similar chemical compositions, all diets were isonitrogenous.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was no difference in palatability and preference of feed containing or not 3% FPM (Table 5). Santos et al (2015) reported an increase in DM intake in sheep consuming diets with increasing levels of mesquite pod meal and attributed this behavior to the taste of the food as well as due to the reduction in NDF content of diets. In agreement with Valadares Filho (2006), sugars present in mesquite pod are composed of 75% sucrose.…”
Section: Parametermentioning
confidence: 99%